2018
DOI: 10.1152/ajprenal.00057.2018
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of folate-conjugated rapamycin versus unconjugated rapamycin in an orthologous mouse model of polycystic kidney disease

Abstract: Autosomal-dominant polycystic kidney disease (ADPKD) is a very common genetic disease leading to renal failure. Numerous aberrantly regulated signaling pathways have been identified as promising molecular drug targets for ADPKD therapy. In rodent models, many small-molecule drugs against such targets have proven effective in reducing renal cyst growth. For example, mammalian target of rapamycin (mTOR) inhibition with rapamycin greatly ameliorates renal cystic disease in several rodent models. However, clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…The great efficacy of rapamycin derivatives in several mouse models of PKD raised hope for a cure for these devastating diseases 2,3,7,66 . In human clinical trials, rapamycin derivatives blunted angiomyolipoma growth in TSC patients 67 , while the results for ADPKD were moderate or negative [68][69][70] .…”
Section: Discussionmentioning
confidence: 99%
“…The great efficacy of rapamycin derivatives in several mouse models of PKD raised hope for a cure for these devastating diseases 2,3,7,66 . In human clinical trials, rapamycin derivatives blunted angiomyolipoma growth in TSC patients 67 , while the results for ADPKD were moderate or negative [68][69][70] .…”
Section: Discussionmentioning
confidence: 99%
“…FRα expression was also found to be high in renal cysts in mouse models of PKD and human ADPKD samples [11, 124], which suggested that PKD could be amenable to FR-targeting strategies. A folate-targeted form of the mTORC1 inhibitor (see above) rapamycin ( FC-rapa or EC0371 ) was developed that included a hydrophilic spacer and a self-immolative linker designed to be cleaved intracellularly to reconstitute the active drug [11].…”
Section: Molecular Targets On the Horizonmentioning
confidence: 99%
“…Both, FC-rapa and unconjugated rapamycin were similarly effective in inhibiting PKD disease progression. However, FC-rapa exhibited much reduced extra-renal effects, including effects on the immune system and reduced systemic toxicity as assessed by body weight gain over time [124]. In the same study, it could also be directly demonstrated that renal cysts are accessible to folate-conjugated compounds as assessed using a novel fluorescent folate-conjugated reporter [124].…”
Section: Molecular Targets On the Horizonmentioning
confidence: 99%
See 2 more Smart Citations